Meningkatkan Sikap Sosial Melalui Penggunaan Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Siswa Sekolah Dasar - Harum Suprianingsih; Rizki Ananda; Musnar Indra Daulay (Universitas Negeri Makassar, 2023)
. This research is motivated by the low social attitudes of fourth grade students. This research is a Classroom Action (PTK). The subjects of this study were students of class IVC SD Negeri 032 Kualu totaling 29 students, consisting of 17 male students and 12 female students. The results of the average individual completeness assessment of students' social attitudes in the first cycle of the first meeting reached 68.39% with classical completeness 51.7%, the second meeting with an average individual completeness of 77.27% with classical completeness 62.1%. Then continued with the second cycle, the average individual completeness of the first meeting reached 79.89% with classical completeness of 79.3%, then continued at the second meeting with an average of individual mastery reaching 81.03% with classical completeness of 86.2%. thus, it can be concluded that the use cooverative learning type of team games tournament (TGT) can improve the social attitudes of elementary school students.